Dignità della persona: La prospettiva buddhista - Busacchi, Vinicio (Dignità umana, 2024)
In Buddhism the idea of human dignity is a key concept. However, several factors contribute to making its exact understanding complex – for example, the substantial lack of unity of Buddhist schools and traditions. This article examines the various doctrinal aspects and key issues of these traditions, with particular emphasis on the Mahāyāna. Some new interpretations tend to intertwine the question of human dignity with the question of human rights.